Formação e trajetória político-eleitoral do Movimento Democrático Brasileiro (MDB) em Cachoeiro de Itapemirim (1966-1979) - Andrade, Aline Guimarães (2018)
The purpose of this dissertation is to analyze the political-electoral performance of the Brazilian Democratic Movement (MDB) between 1966 and 1979 in comparison to the National Renewal Alliance (ARENA), especially in the municipality of Cachoeiro de Itapemirim ES, in the elections the majority of whom were members of the executive and municipal legislature, given that the current political situation was bipartisanism, implemented after the civil-military coup in 1964 and in force between 1966 and 1979. To that end, some characters who were corroborated in the construction of the MDB party in Cachoeiro de Itapemirim were also mentioned, as well as helping to emerge victorious in different lawsuits during the course of bipartisanship. The dissertation was based on multiple documentary research, which demonstrated that the formation of the Cachoeirense MDB was mainly characterized by a less conservative wing of former members of different parties such as PSB and PSP, in addition to PTB. On the other hand, most of the petebistas considered more conservative, like Raymundo Andrade, were directed towards the Arena. From the formation of the MDB in Cachoeiro de Itapemirim, through its main characters, the paper seeks to analyze the electoral processes of the bipartisan period, which gave the MDB important victories even before the so-called "emedebista turn" of 1974, highlighting the motivations for such a feat.